The role of microRNAs in pathophysiology and diagnostics of metabolic complications in obstructive sleep apnea patients - Karuga, Filip Franciszek; Jaromirska, Julia; Malicki, Mikołaj; Sochal, Marcin; Szmyd, Bartosz; Białasiewicz, Piotr; Strzelecki, Dominik; Gabryelska, Agata (Frontiers in Molecular Neuroscience, 2023)
Obstructive sleep apnea (OSA) is one of the most common sleep disorders, which is characterized by recurrent apneas and/or hypopneas occurring during sleep due to upper airway obstruction. Among a variety of health consequences, OSA patients are particularly susceptible to developing metabolic complications, such as metabolic syndrome and diabetes mellitus type 2. MicroRNAs (miRNAs) as epigenetic modulators are promising particles in both understanding the pathophysiology of OSA and the prediction of OSA complications. This review describes the role of miRNAs in the development of OSA-associated metabolic complications. Moreover, it summarizes the usefulness of miRNAs as biomarkers in predicting the aforementioned OSA complications.